Sustainable poultry development in the tropics: Lessons on South-South collaboration from ILRI’s Tropical Poultry Genetics Solutions Program - Dessie, Tadelle; Zewdie, Yihenew (International Livestock Research Institute, 2022)
The Tropical Chicken Genetics Solutions (TPGS) initiative and its partners held a two-day workshop on 7–8 July 2022, at Bahir Dar University, Ethiopia, to document lessons learned from the program and explore opportunities to enhance the effectiveness of complementary chicken-based interventions. The workshop also proposed business models for improving the performance of chicken value chains. TPGS is a genetics innovation strategy for identifying and testing high-producing farmer-preferred poultry genotypes and using them at scale to address income, nutrition and empowerment challenges in Africa, Asia and beyond.